2023
DOI: 10.1101/2023.04.26.537486
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved gene annotation of the fungal wheat pathogenZymoseptoria triticibased on combined Iso-Seq and RNA-Seq evidence

Abstract: Despite large omics datasets, the establishment of a reliable gene annotation is still challenging for eukaryotic genomes. Here, we used the reference genome of the major fungal wheat pathogen Zymoseptoria tritici (isolate IPO323) as a case study to develop methods to improve eukaryotic gene prediction. Four previous IPO323 annotations identified 10,933 to 13,260 gene models, but only one third of these coding sequences (CDS) have identical structures. To resolve these discrepancies and improve gene models, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 101 publications
0
11
0
Order By: Relevance
“…Comparison with the new annotation of the reference genome [52], in which similar numbers of sense and antisense lncRNAs were found, suggests that technical issues are the most likely cause of the lack of antisense lncRNA in our predictions. In some cases, reads originating from the loci in the new annotation are present but at low depth, and/or they do not cover the full length of the transcript [52]. As such, transcripts were not properly assembled and were never assessed by the prediction tool.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Comparison with the new annotation of the reference genome [52], in which similar numbers of sense and antisense lncRNAs were found, suggests that technical issues are the most likely cause of the lack of antisense lncRNA in our predictions. In some cases, reads originating from the loci in the new annotation are present but at low depth, and/or they do not cover the full length of the transcript [52]. As such, transcripts were not properly assembled and were never assessed by the prediction tool.…”
Section: Discussionmentioning
confidence: 55%
“…Despite a clear transition in the sRNA transcriptome under stressful conditions, no direct role in host colonization has been demonstrated for sRNAs, in contrast to several other fungal plant pathosystems [ 51 ]. Recently, an improved genome annotation based on long-read transcript sequencing was established [ 52 ] reporting the production of several lncRNAs during growth in vitro . The study further demonstrated that lncRNAs were differentially expressed between in vitro and in planta conditions, and that some lncRNAs showed interesting expression correlation patterns with nearby genes during infection [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fifth insert, however, does not exhibit any similarity with the type II inserts and was therefore referred to as the type VII insert. Further analysis using the reannotated genome of Z. tritici (Lapalu 2023) revealed that the conserved domains (totaling five) of type II inserts show similarities with retrotransposons from the RLX_Lard_Gridr family (Figure 1B).…”
Section: New Inserts Detected In Pmfs1mentioning
confidence: 99%
“…Aligning the type VI insert sequence on the Z. tritici reference genome (Goodwin et al, 2011(Lapalu et al, 2023 shows 91.57% identity to 89 bp of the internal sequence of another DTX MITE of a total size of 402 bp localized on chromosome 12 (Fig. 2).…”
Section: New Inserts Detected In Pmfs1mentioning
confidence: 99%
See 1 more Smart Citation